Buddhism and Peace Promotion - Gangabhushan M., Molankal (Asia Pacific Journal of Religions and Cultures, 2020)
Increasingly, issues of development with sustainable peace have been occupying a central place in any discussion on development and reform. In present-day society, unrestrained egotism has brought profound disruptions to the human heart and humanity is losing sight of the art of coexisting with nature. While a great deal has been achieved in respect of achieving external material development, however, this is not sufficient as we have not yet succeeded in bringing about peace and happiness or in overcoming suffering. With the advent of increasing violence and materialism in the society, peace promulgation occupies Increasingly, issues of development with sustainable peace have been occupying a central place in any discussion on development and reform. In present-day society, unrestrained egotism has brought profound disruptions to the human heart and humanity is losing sight of the art of coexisting with nature. While a great deal has been achieved in respect of achieving external material development, however, this is not sufficient as we have not yet succeeded in bringing about peace and happiness or in overcoming suffering. With the advent of increasing violence and materialism in the society, peace promulgation occupies a pivotal place. Buddhism advocates that with the promotion of awakening to the interdependent reality, selfish compulsive responses will be replaced by loving -kindness, compassion, sympathetic joy, and equanimity. The degree of kindness, compassion and ympathetic joy largely depends upon the extent of internalization of the teachings of Buddhism. Teachings of Buddhism are pivotal in enhancing the universal values promulgated by Buddha. An active religion working in proximity with people, ave a wider scope to orient the people and demystify the gaps in religious teachings and practices in the society. The paper brings forward the teachings of Buddhism to promote peace.a pivotal place. Buddhism advocates that with the promotion of awakening to the interdependent reality, selfish compulsive responses will be replaced by loving -kindness, compassion, sympathetic joy, and equanimity. The degree of kindness, compassion and sympathetic joy largely depends upon the extent of internalization of the teachings of Buddhism. Teachings of Buddhism are pivotal in enhancing the universal values promulgated by Buddha. An active religion working in proximity with people, have a wider scope to orient the people and demystify the gaps in religious teachings and practices in the society. The paper brings forward the teachings of Buddhism to promote peace.